2005
DOI: 10.1093/bja/aei002
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound guidance in regional anaesthesia †

Abstract: The technology and clinical understanding of anatomical sonography has evolved greatly over the past decade. In the Department of Anaesthesia and Intensive Care Medicine at the Medical University of Vienna, ultrasonography has become a routine technique for regional anaesthetic nerve block. Recent studies have shown that direct visualization of the distribution of local anaesthetics with high-frequency probes can improve the quality and avoid the complications of upper/lower extremity nerve blocks and neuroaxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
269
0
30

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 609 publications
(305 citation statements)
references
References 53 publications
6
269
0
30
Order By: Relevance
“…Despite the recent upsurge in interest, a critical review of the literature reveals that the evidence in favour of improved success with US, compared to traditional nerve localization techniques, is wanting. 3,4,[6][7][8] Existing randomized controlled trials support that US can hasten AXB performance and onset times as well as improve block 'quality' and duration, 3,4,6,8,9 but the ultimate question of improved block success (albeit the definition of 'success' can be highly variable) remains unresolved. Chan et al 10 as well as Liu et al 8 both demonstrated improved success rates using US compared to peripheral nerve stimulation (PNS) for AXB.…”
mentioning
confidence: 99%
“…Despite the recent upsurge in interest, a critical review of the literature reveals that the evidence in favour of improved success with US, compared to traditional nerve localization techniques, is wanting. 3,4,[6][7][8] Existing randomized controlled trials support that US can hasten AXB performance and onset times as well as improve block 'quality' and duration, 3,4,6,8,9 but the ultimate question of improved block success (albeit the definition of 'success' can be highly variable) remains unresolved. Chan et al 10 as well as Liu et al 8 both demonstrated improved success rates using US compared to peripheral nerve stimulation (PNS) for AXB.…”
mentioning
confidence: 99%
“…Alternatively, ultrasound guidance can be used for needle placement. Ultrasonography plays an important role in aiding regional nerve and peripheral-nerve blocks (19)(20)(21)(22). Greher et al reported a high success rate, clinical feasibility, and usefulness of ultrasound-guided lumbar medial branch blocks (11,23).…”
Section: Discussionmentioning
confidence: 99%
“…Real-time ultrasound guidance during nerve blockade decreases the risks associated with improper needle placement. 1,2 Nerve block simulation training before direct patient practice has demonstrated a reduction in procedural length and improvement of outcomes. 3,4 However, most low-fidelity nerve block models, although able to simulate the visual appearance of a nerve, are unable to mimic the sonographic findings of the injection of an anesthetic agent.…”
Section: Introductionmentioning
confidence: 99%